Mathematical Understanding Concept Ability of Junior High School Students on Algebra - Lubis, Mara Samin; Br Ginting, Siti Salamah; Wahyuni, Fitry (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2024)
Abstract:Mathematical understanding concept ability must be possessed by students in learning mathematics. This study describes students' ability to understand algebraic concepts. The research method used was qualitative research with research subjects of 30 grade VII MTs TPI Sawit Seberang students. Data was collected through observation, interviews, and documentation. The results showed that students' ability to understand mathematical concepts was still low. Only two indicators have a good rate, namely restating the concept by 67% and giving examples instead of examples by 60%. Students have difficulty in distinguishing elements of algebraic forms, substituting equations, and calculating operations in algebraic form. Schools must be able to facilitate students in learning activities so that students have a good understanding of mathematical concepts. Abstrak:Kemampuan pemahaman konsep matematika harus dimiliki siswa dalam belajar matematika. Penelitian ini mendeskripsikan kemampuan siswa memahami konsep aljabar. Metode penelitian yang digunakan adalah penelitian kualitatif dengan subyek penelitian 30 siswa kelas VII MTs TPI Sawit Seberang. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan kemampuan pemahaman konsep matematika siswa masih rendah. Hanya dua indikator yang tingkat ketercapaiannya bagus, yakni menyatakan ulang konsep sebesar 67% dan memberi contoh dan bukan contoh sebesar 60%. Siswa kesulitan dalam membedakan unsur-unsur bentuk aljabar, mensubstitusi persamaan, dan menghitung operasi dalam bentuk aljabar. Sekolah harus mampu memfasilitasi siswa dalam kegiatan pembelajaran sehingga siswa memiliki pemahaman konsep matematika yang baik.